Eccentric compression behaviour of concrete columns reinforced with steel-FRP composite bars. (1st July 2021) - Ge, Wenjie; Chen, Kangbao; Guan, Zhongwei; Ashour, Ashraf; Lu, Weigang; Cao, Dafu
Highlights: Eccentric compression behaviour of RC columns reinforced by SFCBs was investigated. Moment magnification factor, bearing capacity and crack width formulae were proposed. The effect of various parameters on the eccentric compression behaviour was studied. Abstract: Eccentric compression behaviour of reinforced concrete (RC) columns reinforced by steel-FRP composite bars (SFCBs) was investigated through experimental work and theoretical analyses. The tension and compression test results show that SFCBs demonstrate a stable post-yield stiffness. The mechanical properties of the composite reinforcement have a significant influence on eccentric compression behaviour of the reinforced concrete columns, in terms of failure mode, crack width, deformation and bearing capacity. Formulae were also developed to discriminate failure mode and to determine moment magnification factor, bearing capacity and crack width of the columns studied, with the theoretical predictions being in a good agreement with the experimental results. In addition, parametric studies were conducted to evaluate the effects of mechanical properties of reinforcement, reinforcement ratio, eccentricity, slenderness ratio, types of reinforcement and concrete on the eccentric compression behaviour of RC columns. The results show that the compressive performance is significantly improved by using the high performance concrete, i.e. reactive powder concrete (RPC) and engineered cementious composites (ECC).